Survival Trends in Patients Under Age 65 Years With Mantle Cell Lymphoma, 1995–2016: A SEER-Based Analysis - Hongyu Wu; Hongyu Wu; Hongyu Wu; Jianwei Wang; Jianwei Wang; Jianwei Wang; Xuanye Zhang; Xuanye Zhang; Xuanye Zhang; Hang Yang; Hang Yang; Hang Yang; et al. (Frontiers in Oncology, 2020)
Purpose: The treatment paradigm for mantle cell lymphoma (MCL), a B-cell malignancy, has shifted considerably during the past decades. This study aimed to evaluate time trends in overall survival (OS) and disease-specific mortality (DSM) of younger (age ≤ 65 years) patients with MCL from 1995 to 2016.Methods: We used the Surveillance, Epidemiology, and End Results database. Year of diagnosis was divided into three eras: the chemotherapy-alone era (1995–2000), intensified-immunochemotherapy era (2001–2012), and targeted-therapy era (2013–2016). We used the Kaplan–Meier method, log-rank test, and subdistribution proportional hazard regression in the analysis.Results: A total 4,892 patients were identified. Median OS increased from 67 months in the chemotherapy-alone era to 107 months in the intensified-immunochemotherapy era (P < 0.001). The DSM rate decreased significantly from 1995 to 2016 (P < 0.001); the adjusted hazard ratios of MCL-specific death were 0.589 (P < 0.001) for the intensified-immunochemotherapy era and 0.459 (P < 0.001) for targeted-therapy era, as compared with the chemotherapy-alone era. Patients with advanced-stage MCL exhibited lowering risk of death across the three eras (P < 0.001).Conclusions: During 1995–2016, survival in younger patients with MCL increased significantly, especially those with advanced-stage disease, potentially reflecting the impact of advancement in treatment modalities on MCL outcome.